Updated EAU Guidelines for Clear Cell Renal Cancer Patients Who Fail VEGF Targeted Therapy - Powles, Thomas; Staehler, Michael; Ljungberg, Börje; Bensalah, Karim; Canfield, Steven E; Dabestani, Saeed; Giles, Rachel; Hofmann, Fabian; Hora, Milan; Kuczyk, Markus A; Lam, Thomas; Marconi, Lorenzo; et al. (European urology, 2016)
The European Association of Urology renal cancer guidelines have been updated to recommend nivolumab and cabozantinib over the previous standard of care in patients who have failed one or more lines of VEGF targeted therapy.
Keywords: Anilides; everolimus; nádory ledvin; Retreatment; Treatment Failure; monoklonální protilátky; nivolumab; neúspěšná terapie; protinádorové látky; Everolimus; karcinom z renálních buněk; Kidney Neoplasms; Practice Guidelines as Topic; Nivolumab; lidé; anilidy; Humans; opakovaná terapie; pyridiny; Pyridines; Carcinoma, Renal Cell; vaskulární endoteliální růstový faktor A; Vascular Endothelial Growth Factor A; Antibodies, Monoclonal; Antineoplastic Agents; směrnice pro lékařskou praxi jako téma